Environmental bioaerosol surveillance as an early warning system for pathogen detection in North Carolina swine farms: A pilot study. Issue 2 (29th June 2020) - Anderson, Benjamin D.; Yondon, Myagmarsukh; Bailey, Emily S.; Duman, Ege K.; Simmons, Ryan A.; Greer, Annette G.; Gray, Gregory C.
Abstract: Disease outbreaks can readily threaten swine production operations sometimes resulting in large economic losses. Pathogen surveillance in swine farms can be an effective approach for the early identification of new disease threats and the mitigation of transmission before broad dissemination among a herd occurs. Non‐invasive environmental bioaerosol sampling could be an effective and affordable approach for conducting routine surveillance in farms, providing an additional tool for farmers to protect their animals and themselves from new disease threats. In this pilot study, we implemented a non‐invasive, prospective bioaerosol sampling strategy in a swine farm located in the United States to detect economically important swine pathogens. Farm personnel collected air samples from two swine barns for 23 weeks between July and December 2017. Samples were then tested within 24 hr of collection by molecular techniques for a number of economically important swine pathogens. Of the 86 bioaerosol samples collected, 4 (4.7%) were positive for influenza A, 1 (1.2%) was positive for influenza D, 13 (15.1%) were positive for PCV2, and 13 (15.1%) were positive for PCV3. Overall, this pilot study showed that our bioaerosol surveillance strategy was feasible and able to generate data that could be quickly disseminated back to the farm stakeholders (within 24 hr). We were also able to identify PCV2, PCV3 and influenza A virus in air samples as clinical disease became apparent in the pigs, strongly suggesting that bioaerosol sampling can be used as an effective non‐invasive surveillance approach for the detection of multiple pathogens in this and likely other animal production environments.